a = r = 0 ∑ n [ ( r n ) 1 ] .
Find the value of
r = 0 ∑ n [ ( r n ) r ]
in terms of a and n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We can write a as a = ( 0 n ) 1 + ( 1 n ) 1 + ( 2 n ) 1 + ⋯ + ( n − 2 n ) 1 + ( n − 1 n ) 1 + ( n n ) 1
Let the required summation be S .
S = ( 0 n ) 0 + ( 1 n ) 1 + ( 2 n ) 2 + ⋯ + ( n − 2 n ) n − 2 + ( n − 1 n ) n − 1 + ( n n ) n
As we keep subtracting a from S , note that each coefficient reduces by 1.
S − a S − 2 a ⋮ S − n a = ( 0 n ) − 1 + ( 1 n ) 0 + ( 2 n ) 1 + ⋯ + ( n − 2 n ) n − 3 + ( n − 1 n ) n − 2 + ( n n ) n − 1 = ( 0 n ) − 2 + ( 1 n ) − 1 + ( 2 n ) 0 + ⋯ + ( n − 2 n ) n − 4 + ( n − 1 n ) n − 3 + ( n n ) n − 2 ⋮ ⋮ ⋮ ⋮ ⋮ ⋮ = ( 0 n ) − n + ( 1 n ) − ( n − 1 ) + ( 2 n ) − ( n − 2 ) + ⋯ + ( n − 2 n ) − 2 + ( n − 1 n ) − 1 + ( n n ) − 0
Observe that the coefficients in S − n a are similar to the coefficients in S . We can use the property of binomial coefficients , ( r n ) = ( n − r n ) to see that S − n a is in fact equal to − S .
S − n a S − n a S − n a S − n a = ( n n ) − n + ( n − 1 n ) − ( n − 1 ) + ( n − 2 n ) − ( n − 2 ) + ⋯ + ( 2 n ) − 2 + ( 1 n ) − 1 + ( 0 n ) − 0 = − ( ( n n ) n + ( n − 1 n ) ( n − 1 ) + ( n − 2 n ) ( n − 2 ) + ⋯ + ( 2 n ) 2 + ( 1 n ) 1 + ( 0 n ) 0 ) = − ( ( 0 n ) 0 + ( 1 n ) 1 + ( 2 n ) 2 + ⋯ + ( n − 2 n ) n − 2 + ( n − 1 n ) n − 1 + ( n n ) n ) = − S
Since S − n a = − S , we see that S = 2 n a □
If n is odd, we can rewrite ∑ r = 0 n ⎣ ⎡ ( n r ) r ⎦ ⎤ as ∑ r = 0 2 n − 1 ⎣ ⎡ ( n r ) r ⎦ ⎤ + ⎣ ⎡ ( n n − r ) n − r ⎦ ⎤ , so we're pairing the first with the last, the second with the penultimate, until we get to the middle. As n is odd, we're pairing an even number of terms.
As we know that ( n r ) = ( n n − r ) , the sum can be simply written as ∑ r = 0 2 n − 1 ⎣ ⎡ ( n r ) n ⎦ ⎤ , which is equal to n ⋅ ∑ r = 0 2 n − 1 ⎣ ⎡ ( n r ) 1 ⎦ ⎤
Basing on the same propertie as above, we note that 2 a = ∑ r = 0 2 n − 1 ⎣ ⎡ ( n r ) 1 ⎦ ⎤
Thus, ∑ r = 0 n ⎣ ⎡ ( n r ) n ⎦ ⎤ = 2 n a
If n is even, we do the pairing terms process as follows:
∑ r = 0 n ⎣ ⎡ ( n r ) n ⎦ ⎤ = ( n n / 2 ) n / 2 + ∑ r = 0 2 n − 1 ⎣ ⎡ ( n r ) r ⎦ ⎤ + ⎣ ⎡ ( n n − r ) n − r ⎦ ⎤ = 2 ( n n / 2 ) n + ∑ r = 0 2 n − 1 ⎣ ⎡ ( n r ) n ⎦ ⎤ = n ⎝ ⎛ 2 ( n n / 2 ) 1 + ∑ r = 0 2 n − 1 ⎣ ⎡ ( n r ) 1 ⎦ ⎤ ⎠ ⎞
And we can rewrite the last sum as
n ⎝ ⎛ 2 1 ∑ r = 0 n ⎣ ⎡ ( n r ) 1 ⎦ ⎤ ⎠ ⎞ = 2 n a
There's actually a simpler way to do the pairing for both the cases of even and odd n , which is much similar to how Gauss found the closed form for the sum of first n natural numbers.
Define S : = r = 0 ∑ n ( r n ) r . Now, consider the double of the sum S .
2 S = ( r = 0 ∑ n ( r n ) r ) + ( r = 0 ∑ n ( n − r n ) n − r )
By the reflection property of the binomial coefficients, i.e., ( r n ) = ( n − r n ) , we have,
2 S = r = 0 ∑ n ( r n ) r + n − r = r = 0 ∑ n ( r n ) n = n a ⟹ S = 2 n a
Problem Loading...
Note Loading...
Set Loading...
Let us assume that ∑ r = 0 n ( r n ) 1 = a Now we examine the sum S 1 = ∑ r = 0 n ( r n ) r and the sum S 2 = ∑ r = 0 n ( n − r n ) n − r clearly S 1 = S 2 and considering the identity ( r n ) = ( n − r n ) it follows that 2 S 1 = S 1 + S 2 = ∑ r = 0 n ( r n ) r + ∑ r = 0 n ( n − r n ) n − r = ∑ r = 0 n ( r n ) n = n ∑ r = 0 n ( r n ) 1 = a n and thus S 1 = 2 a n